Psychology of dysfunctional family (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Dysfunctional family a family in which relationships or communication are impaired and members are unable to attain closeness and self-expression. Members of a dysfunctional family often develop symptomatic behaviors, and often one individual in the family presents as the identified patient.